Artificial Intelligence and the Future of International Trade Law: Balancing Innovation, Regulation, and Global Fairness - Md Samirul Islam; Abu Sayed; Anika Mahjabin; Nur Nahar Rimi (Legalis : Journal of Law Review, 2026)
The international trade system will see the growing influence and use of artificial intelligence (AI), which has had important implications for regulation, decision-making, as well as global governance on both sides of borders. Building on legitimacy theory, this research provides the first empirical evidence of how AI knowledge competences, perceived ethical and transparency standards of AI, global fairness concerns over them and trust in AI impact governance alignment and how such governance alignment drives support for integrating AIs into international trade law. A quantitative study was designed in the form of a survey administered to U.S. policymakers, legal experts, business professionals and scholars. Following data screening, 320 returned cases were considered in Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that all the four antecedents variables, namely firm scope, power asymmetry, strategic interpenetration and home country legitimacy, have a positive impact on governance alignment. Governance alignment is shown to have a significant direct impact on AI integration in international trade law, and it also strongly mediates the relationships between AI talent competencies, ethical and transparency standards, global fairness concerns, trust in AI and AI integration. The results emphasize governance alignment as a core mechanism. By doing so, it offers empirical evidence for the institutional and ethical requirements needed for responsible AI adoption in international trade law, while providing policy-relevant insights addressing the challenge of fostering innovation while ensuring fairness, transparency and global equity.